The effects of human papillomavirus vaccination in Japan - Choi, Wongyeong; Shim, Eunha (Human vaccines & immunotherapeutics, 2025)
Human papillomavirus (HPV) is a prevalent virus responsible for nearly all cervical cancer cases, a major health issue worldwide, including in Japan. With over 12,000 cases of cervical cancer and 4,213 related deaths annually in Japan, effective prevention through vaccination is essential. The 9-valent HPV (9vHPV) vaccine provides broader protection against high-risk HPV types (HPV-31, -33, -45, -52, -58) compared to the bivalent and quadrivalent (4vHPV) vaccines. This study evaluates the public health impact of both girls-only and gender-neutral vaccination strategies using 9vHPV and 4vHPV vaccines in Japan. A dynamic transmission model, calibrated with Japanese population data, was used to project cervical cancer and genital wart outcomes over 100 years. Vaccination scenarios included no vaccination, girls-only and gender-neutral vaccination with both 4vHPV and 9vHPV vaccines. Results show that switching to the 9vHPV vaccine significantly reduces cervical cancer incidence and mortality compared to 4vHPV, particularly in gender-neutral strategies. The 9vHPV vaccine was projected to prevent an additional 857,549 cases of cervical intraepithelial neoplasia (CIN2/3) and 43,799 cervical cancer deaths in a girls-only vaccination strategy compared to the 4vHPV vaccine, over a 100-y period. Gender-neutral vaccination with the 9vHPV further amplifies these benefits, with a faster reduction in HPV-related diseases for both genders. Even under conservative assumptions of 20-y vaccine protection, 9vHPV outperformed 4vHPV in all scenarios. These findings support switching to the 9vHPV vaccine and expanding the National Immunization Program to include boys to achieve long-term HPV control, reduce HPV-related cancers, and improve public health outcomes in Japan.